2005
DOI: 10.1063/1.2128494
|View full text |Cite
|
Sign up to set email alerts
|

Transverse and longitudinal space-charge-induced broadenings of ultrafast electron packets

Abstract: High brightness ultrafast electron sources are limited by space-charge effects. In the high-electron-density regime, Coulomb repulsion induces both transverse and longitudinal broadenings of electron packets. We describe a three-dimensional mean-field model, which takes into account Coulomb repulsion in all directions. Measurements of spatial electron pulse widths are carried out after extraction from a photoemission electron gun. Experiments and simulation results are in very good agreement. Coulomb repulsion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 14 publications
3
26
0
Order By: Relevance
“…Theoretical and experimental works on short electron pulses [27][28][29] and photoemission 30,31 have shown that similar space charge problems also appear at a threshold around 2 e / m 2 pulse, 27 in good agreement with our results. Generally, it was found that while longitudinal broadening of electron pulses can be very significant at the values found also in our case, energy broadening would typically be up to a few eV.…”
Section: Resultssupporting
confidence: 92%
“…Theoretical and experimental works on short electron pulses [27][28][29] and photoemission 30,31 have shown that similar space charge problems also appear at a threshold around 2 e / m 2 pulse, 27 in good agreement with our results. Generally, it was found that while longitudinal broadening of electron pulses can be very significant at the values found also in our case, energy broadening would typically be up to a few eV.…”
Section: Resultssupporting
confidence: 92%
“…This leads to Coulomb repulsion, which manifests itself in three ways: temporal, lateral, and energy broadening, resulting in significant blurring of the images. Theoretical and experimental work on short electron pulses and photoemission have shown similar space charge problems, in good quantitative agreement with our results [43][44][45][46][47]. Our results are also comparable to those obtained using the femtosecond XUV pulses from the free-electron laser FLASH [48].…”
Section: Experimental Setup and Requirementssupporting
confidence: 82%
“…While the electron microscope features a myriad of magnetostatic lenses, electrostatic lenses, deflection coils, stigmator coils and pinholes, the column of our UED or UEC instruments, containing just a single magnetostatic lens, seems fairly simple by comparison. Theoretical studies to date [7][8][9][10][11] have treated electron pulses for diffraction and imaging primarily in the absence of focusing fields, thereby relying on several assumptions to match experimental data, which could be violated in reality.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the electron pulses in the presence of space-charge will be modeled with typical UED or UEC parameters using two approaches: a mean field model 7,8,10 and an N-body Monte Carlo simulation. 12 The mean field model will be expanded to allow for the incorporation of pulse shaping fields.…”
Section: Introductionmentioning
confidence: 99%